Semi Unit Graphs of Commutative Semi Rings - Ahmed, Yaqoub; Aslam, M. (Communications in Mathematics and Applications, 2019)
In this article, we introduce semi unit graph of semiring \(S\) denoted by \(ξ(S)\). The set of all elements of $S$ are vertices of this graph where distinct vertices \(x\) and \(y\) are adjacent if and only if \(x+y\) is a semiunit of \(S\). We investigate some of the properties and characterization results on connectedness, distance, diameter, girth, completeness and connectivity of \(ξ(S)\).